Comparison of multileaf collimator and conventional circular collimator systems in Cyberknife stereotactic radiotherapy. (13th February 2017) - Murai, Taro; Hattori, Yukiko; Sugie, Chikao; Iwata, Hiromitsu; Iwabuchi, Michio; Shibamoto, Yuta
Abstract: Multileaf collimator (MLC) technology has been newly introduced with the Cyberknife system. This study investigated the advantages of this system compared with the conventional circular collimator (CC) system. Dosimetric comparisons of MLC and CC plans were carried out. First, to investigate suitable target sizes for the MLC mode, MLC and CC plans were generated using computed tomography (CT) images from 5 patients for 1, 3, 5 and 7 cm diameter targets. Second, MLC and CC plans were compared in 10 patients, each with liver and prostate targets. For brain targets, doses to the brain could be spared in MLC plans better than in CC plans ( P ≤ 0.02). The MLC mode also achieved more uniform dose delivery to the targets. The conformity index in MLC plans was stable, irrespective of the target size ( P = 0.5). For patients with liver tumors, the MLC mode achieved higher target coverage than the CC mode ( P = 0.04). For prostate tumors, doses to the rectum and the conformity index were lowered in MLC plans compared with in CC plans ( P ≤ 0.04). In all target plans, treatment times in MLC plans were shorter than those in CC plans ( P < 0.001). The newly introduced MLC technology can reduce treatment time and provide favorable or comparable dose distribution for 1–7 cm targets. In particular, the MLC mode has dosimetric advantage for targets near organs at risk. Therefore, the MLC mode is recommended as the first option in stereotactic body radiotherapy.